Properties of quadripartitioned neutrosophic interval-valued set to the reciprocal fraction function via various operators - M.Palanikumar; Nasreen Kausar; Cuauhtemoc Samaniego (Neutrosophic Sets and Systems)
A novel technique used to generate quadripartitioned neutrosophic interval-valued sets applied to the reciprocal fraction function is presented in this paper. A new extension of neutrosophic interval-valued sets and interval-valued fuzzy sets are quadripartitioned neutrosophic interval-valued sets. Quadripartitioned neutrosophic interval-valued weighted averaging, geometric, and generalized concepts will all be covered in this article. To obtain the weighted average and geometric, we employed an aggregating model. Using algebraic approaches, a number of sets with significant properties will be further examined.